Absence of Wharton’s jelly around an umbilical artery - Wade, Mouhamadou; Gueye, Mamour; Mbodji, Aissatou; Ndiaye, Mame D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Wharton’s jelly is a mucoid, avascular and connective tissue which plays the role of umbilical vessels protection. Its absence exposes to poor neonatal outcomes or fetal death. We report a rare case of Absence of Wharton’s Jelly, diagnosed by examination of the placenta the examination with a live fetus.